Musical Expertise Modulates Early Processing of Syntactic Violations in Language - Fitzroy, Ahren B.; Sanders, Lisa D. (Frontiers in Psychology, 2013)
Syntactic violations in speech and music have been shown to elicit an anterior negativity (AN) as early as 100 ms after violation onset and a posterior positivity that peaks at roughly 600 ms (P600/LPC). The language AN is typically reported as left-lateralized (LAN), whereas the music AN is typically reported as right-lateralized (RAN). However, several lines of evidence suggest syntactic processing of language and music rely on overlapping neural systems. The current study tested the hypothesis that syntactic processing of speech and music share neural resources by examining whether musical proficiency modulates ERP indices of linguistic syntactic processing. ERPs were measured in response to syntactic violations in sentences and chord progressions in musicians and nonmusicians. Violations in speech were insertion errors in normal and semantically impoverished English sentences. Violations in music were out-of-key chord substitutions from distantly and closely related keys. Phrase-structure violations elicited an AN and P600 in both groups. Harmonic violations elicited an LPC in both groups, blatant harmonic violations also elicited a RAN in musicians only. Cross-domain effects of musical proficiency were similar to previously reported within-domain effects of linguistic proficiency on the distribution of the language AN; syntactic violations in normal English sentences elicited a left-lateralized AN in musicians and a bilateral AN in nonmusicians. The late positivities elicited by violations differed in latency and distribution between domains. These results suggest that initial processing of syntactic violations in language and music relies on shared neural resources in the general population, and that musical expertise results in more specialized cortical organization of syntactic processing in both domains.